Acute effects of resisted and assisted sprint training on trained team athletes - Tan, Jing Wei (Nanyang Technological University, 2022)
Resisted sprint training (RST) overloads the physiological aspects and increases stride length and assisted sprint training (AST) overloads the neuromuscular system to induce higher stride frequency. This study will use uphill and downhill sprinting, as there is a lack of studies that focus on this form of sprint training. The aim of this study is to investigate the acute effects uphill and downhill sprint training in trained team athletes. 11 female varsity handball athletes (Age 20.7±1.0 years) were randomly assigned to the AST or RST group and performed 3 sessions of either uphill or downhill sprinting, and two 40m straight line sprint tests for their pre-test and post-test. The AST and RST group sprinted downhill and uphill respectively at 80% maximal effort 5 times per intervention session on a slope of 3° angle. Split timings of the 40m sprint were collected using Speedlight Timing Gates and 0-5m, 5-10m, 10-20m acceleration and maximum velocity (MV) were calculated using Microsoft Excel. All statistical analyses were done on JASP. Repeated Measures ANOVA revealed significant improvement in 0-5m acceleration (F(1,8)=7.072, p=0.029, ηp2=0.469), but no significant change (p>0.05) in 10-20m acceleration from pre-test to post-test. Friedman test and Mann-Whitney U test revealed no significant changes in 5-10m acceleration and MV from pre-test to post-test. No significant differences were reported between RST and AST. Accordingly, these results suggest that 3 sessions of uphill or downhill sprinting may be insufficient to elicit the necessary overload required.